2018
DOI: 10.1038/s41418-018-0114-7
|View full text |Cite
|
Sign up to set email alerts
|

Integrin α6β4-Src-AKT signaling induces cellular senescence by counteracting apoptosis in irradiated tumor cells and tissues

Abstract: Cellular senescence refers to an irreversible growth arrest that is triggered by various intrinsic and extrinsic stresses. Many recent studies have demonstrated that cellular senescence plays a crucial role in the regression of tumors exposed to ionizing radiation (IR), but the underlying mechanism remains unknown. Here we show that the activation of integrin β4 is essential for IR-induced cellular senescence. IR treatment results in the phosphorylation of integrin β4 at tyrosine residue 1510, leading to activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 63 publications
5
26
0
Order By: Relevance
“…By RNA interference, ITGB4 deficiency inhibits the cell division cycle and proliferation in vitro . ITGB4 has also been shown to be associated with aging in many different cells . Here, our results also verified that ITGB4 deficiency induced senescence‐like changes of airway epithelial cells in vivo and in vitro .…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…By RNA interference, ITGB4 deficiency inhibits the cell division cycle and proliferation in vitro . ITGB4 has also been shown to be associated with aging in many different cells . Here, our results also verified that ITGB4 deficiency induced senescence‐like changes of airway epithelial cells in vivo and in vitro .…”
Section: Discussionsupporting
confidence: 80%
“…Besides, it has also been demonstrated that after house dust mite stress, ITGB4 defects in airway epithelial cells conferred increased airway hyper‐responsiveness and aggravated airway inflammation compared with wild‐type mice . Notably, ITGB4 has also been shown to be associated with senescence in many different cells . Senescence is controlled by two major senescence pathways, p53–p21 WAF1/CIP1 and Rb–p16 INK4a13 .…”
Section: Introductionmentioning
confidence: 99%
“…Integrins are the key players in tumor cell spread and are expressed at different levels at different stages of tumor development. Dysregulation of integrins can alter their functions, causing tumor cells to detach from the basement membrane and lose polarity, and these increased free integrins participate in bidirectional signal transduction in tumors [46][47][48] . Two key proteins, FAK and Src, important regulatory proteins affected by integrin α6β4, are closely related to tumor growth and metastasis and are activated through a series of phosphorylation events.…”
Section: Eno1 Is Transferred Between Hcc Cells Via Exosomes To Promotmentioning
confidence: 99%
“…The senescent cells become flat and enlarged due to rearrangement of the cytoskeleton. Their plasma membrane composition is changed by the up-regulation of caveolin-1, a main component of caveolae (34, 35). Senescent cells also have an increased cholesterol content in membrane and large and dysfunctional mitochondria (34, 35).…”
Section: Key Features Of Celllular Senescencementioning
confidence: 99%
“…Their plasma membrane composition is changed by the up-regulation of caveolin-1, a main component of caveolae (34, 35). Senescent cells also have an increased cholesterol content in membrane and large and dysfunctional mitochondria (34, 35). Lysosomal content and lysosomal enzyme senescence-associated β-galactosidase (SA-β-gal) is highly upregulated during senescence (36).…”
Section: Key Features Of Celllular Senescencementioning
confidence: 99%